Penguatan Pendidikan Karakter Santri melalui Organisasi Ittihadut Thullab Ma’had Riyadlus Sholihin Kota Probolinggo - Husnan, Moh; Khoiriyah, Khoiriyah (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to analyze the role of the ITMARIS student organization (Ittihadut Thullab Ma’had Riyadlus Sholihin) in strengthening character education among students at Riyadlus Sholihin Islamic Boarding School in Probolinggo City. The study is grounded in the need for character development that is not merely normative but also applicative and participatory. ITMARIS serves as a platform for the actualization of character values through students’ direct involvement in structured organizational activities. This research employed a qualitative case study approach, with ITMARIS as the unit of analysis. Data were collected through interviews with organization administrators, students, caregivers, and supervisors, participatory observation, and document analysis. Data validity was ensured through source and technique triangulation, while data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and inductive conclusion drawing. The findings indicate that ITMARIS effectively instills values of responsibility, leadership, independence, discipline, and cooperation among students. Organizational involvement also enhances students’ self-confidence, communication skills, and social relationships. The success of character development is supported by the humanistic and dialogical approach of the supervisors. Despite challenges related to student motivation and limited facilities, ITMARIS sustains its programs through continuous evaluation and innovation, thereby contributing as a contextual and holistic model for character education in Islamic boarding schools.